Napoleon's Russian campaign - Philippe - Paul, Count (Greenwood Press, 1958)
The author, an editor of Campaigns Magazine for ten years, has written a groundbreaking new study of Napoleon's disasterous Russian campaign of 1812. In doing this, he has employed primary sources never before translated from the German and Russian. He points out the real reasons for Napoleon's defeat which had nothing to do with cold weather but rather were a complex combination of faulty logistics, bureaucratic mismanagement and Napoleon's own but uncharacteristic indecision and bad choices.